Obesity Related Indices for Screening of Obesity in Adolescents - Sohani, Amit; Chincholikar, Sanjeev; Patnaik, Bandana; Raje, Swati (Indian Journal of Community Health, 2015)
Background: Obesity is a fast growing problem in the developing countries like India and is now known to be associated with increased health risk. Realizing the fact that the obesity in adolescent age group does not receive the deserved attention in the prevention and control programme, the present study was undertaken on 585 adolescent subjects studying in one college and three schools. Aims and Objectives: 1. To study the prevalence of overweight and obesity in adolescent population. 2. To find the association of body mass index (BMI) with important parameters like skin fold thickness, waist circumference and waist to hip ratio. Methods: It was a cross sectional observational study. The study population was school and college going adolescents in the age group of 11-19 years. The estimated sample size for present study is 585 students. The subjects were screened by body mass index, skin fold thickness, waist circumference and waist to hip ratio. Results: The prevalence of overweight and obesity was 19.14% and 4.44% respectively. It was found that there was strong association between the waist circumference with overweight and obesity. Similarly a strong association between waist to hip ratio with overweight and obesity has been found. Also it was found that there was a strong association between skin fold thickness with overweight and obesity. Skin-fold thickness has more sensitivity as compared to waist circumference and waist to hip ratio. Waist to hip ratio has got maximum specificity amongst all but when both sensitivity and specificity criteria are considered together waist circumference stands out. Conclusion: It was found that the prevalence of overweight and obesity was 19.14% and 4.44% respectively. Skin-fold thickness has more sensitivity as compared waist circumference and waist to hip ratio. Waist to hip ratio has got maximum specificity. When sensitivity and specificity criteria are considered together waist circumference can be effectively used as screening tool